Age is not just a number—Mathematical model suggests senescence affects how fish populations respond to different fishing regimes. Issue 19 (7th September 2021) - Ahti, Pauliina A.; Uusi‐Heikkilä, Silva; Marjomäki, Timo J.; Kuparinen, Anna
Abstract: Senescence is often described as an age‐dependent increase in natural mortality (known as actuarial senescence) and an age‐dependent decrease in fecundity (known as reproductive senescence), and its role in nature is still poorly understood. Based on empirical estimates of reproductive and actuarial senescence, we used mathematical simulations to explore how senescence affects the population dynamics of Coregonus albula, a small, schooling salmonid fish. Using an empirically based eco‐evolutionary model, we investigated how the presence or absence of senescence affects the eco‐evolutionary dynamics of a fish population during pristine, intensive harvest, and recovery phases. Our simulation results showed that the presence or absence of senescence affected how the population responded to the selection regime. At an individual level, gillnetting caused a larger decline in asymptotic length when senescence was present, compared to the nonsenescent population, and the opposite occurred when fishing was done by trawling. This change was accompanied by evolution toward younger age at maturity. At the population level, the change in biomass and number of fish in response to different fishery size‐selection patterns depended on the presence or absence of senescence. Since most life‐history and fisheries models ignore senescence, they may be over‐estimating reproductive capacity and under‐estimating natural mortality. Our results highlight the need to understand the combined effects of life‐history characters such as senescence and fisheries selection regime to ensure the successful management of our natural resources. Abstract : Empirical data from Coregonus albula were used to simulate senescence in fish population. The presences or absence of senescence affect the magnitude of fish evolutionary response to fishing and may affect how well the population recovers from fishing.